Physical activity and curriculum development of an after-school gardening program for youth health - Domenghini, Cynthia M. (Kansas State University, 2011)
Public health research shows that targeting behavior directly when promoting healthy behaviors is not as effective for sustainability. Instead the recommendation is to integrate a theoretical framework that identifies factors which affect the targeted behavior and develop the intervention aimed at those factors. The objectives of this dissertation were to measure the healthful benefits of gardening for youth. Strategies were developed for creating an after-school garden club curriculum to target healthy eating, physical activity, sedentary behavior, and gardening. Accelerometers were used to determine physical activity intensity during a garden club session following a curriculum developed to promote physical activity through gardening. In a separate experiment, a portable gas analyzer was used to measure energy expenditure of youth while gardening. The constructs of Social Cognitive Theory were used to provide a guide with strategies for developing a curriculum with a theoretical basis for an after-school garden club targeting overweight prevention. Strategies presented include activities for targeting the theoretical constructs as well as for implementing evaluations. Fourth and fifth grade students at four randomly selected elementary schools in Manhattan, Kansas were invited to join the garden club. Students with parental permission attended the club for ten weeks in the fall and twelve weeks in the spring. During the second year of implementation students with parental permission participated in the accelerometer study. For six days students wore an accelerometer and completed a daily activity log detailing their activities during that time. Students in the fourth and fifth grades from eight Manhattan, Kansas elementary schools were invited to participate in the energy expenditure study during the summer of 2010. Students who participated in this study (n=20) wore a portable gas analyzer and heart rate monitor while performing four gardening tasks. Data were used to calculate energy expenditure of youth while gardening. A theoretically-based after-school garden club curriculum was developed to target increasing youth healthy behaviors. Results from the accelerometer study showed that students were significantly more physically active at the moderate and vigorous intensity level and significantly less sedentary at garden club compared to not at garden club. For students who participated in the energy expenditure study, the gardening tasks (transplanting, weeding, cultivating, and raking) were moderate physical activity (3-5.99 METs). Gardening can be a valuable tool for promoting and increasing physical activity in youth.
Keywords: Social cognitive theory; Youth gardening; Adolescent overweight and obesity; Physical activity; Horticulture (0471)